MORPHOMETRIC CHARACTERISTICS OF INDICATORS OF PHYSICAL DEVELOPMENT OF MALES IN POSTNATAL ONTOGENESIS AND IN CHRONIC ALCOHOLISM (World Bulletin of Public Health, 2024)
The article presents the results of a study on the development and growth of the main parameters of physical development of males during postnatal ontogenesis and in chronic alcoholism. It has been established that this process is uneven and depends on the age characteristics of the body in each age period. In males, the greatest increase in the parameters of physical development is observed in infancy, in elderly and senile men there is a slight decrease in them. In people with chronic alcoholism, there is a noticeable lag in the development of anthropometric parameters compared with the control group, this is most pronounced in old age.
Keywords: physical development; body weight; body length